Decision Making in Foreign Direct Investment: Cases for China and India - Liem , Le Quoc; Wang, Wang Lai (Asian Journal of Empirical Research, 2014)
Foreign direct investment (FDI) seems to be the trend for our global development and culture interaction. Seeing that trend in the world, many companies around the world choose FDI to develop. The FDI markets collect many related data of many projects of the multinational companies, and this research goes with China and India (BRIC countries) as cases to analyze. The results will be mentioned in the following parts of the study which are wage levels and country population and GDP growth affecting decision making in FDI of cases.